Impact of Catheter Choice on Procedural Success of Minimally Invasive Surfactant Therapy - Bhattacharya, Soume; Read, Brooke; Miller, Michael; da Silva, Orlando (American Journal of Perinatology, 2021)
Objective Surfactant delivery via a thin endotracheal catheter during spontaneous breathing; a technique called minimally invasive surfactant therapy (MIST) is an alternative to intubation and surfactant administration. Procedural details among different centers vary, with marked differences in the choice of catheter to instill surfactant. Studies report use of feeding catheters, multiaccess suction catheters, vascular catheters, and more recently custom-built catheters for this purpose. The impact of choice of catheter on procedural success and procedural adverse effects has not been reported. Our present study compares the procedural success and adverse effects of MIST using a semirigid vascular catheter (16G Angiocath-Hobart Method) versus a flexible multiaccess catheter (MAC).Study Design This was a retrospective review of prospectively collected data at a tertiary care neonatal intensive care unit in Southwestern Ontario. All neonates who received surfactant via MIST between May 1, 2016 and September 30, 2020 were included in the study. Relevant baseline characteristics and data on procedural details (premedication, type of catheter, etc.) were collected. The procedural success, number of attempts, and adverse effects between neonates who received MIST via MAC and 16G Angiocath was compared by using Chi-square test or Fisher's test as appropriate. A p-value of less that 0.05 was considered significant.Results A total of 139 neonates received surfactant via MIST method during the study period. Moreover, 93 neonates received the surfactant via MAC, while 46 received it via Angiocath. The baseline demographic characteristics in the two group were similar. A higher proportion of neonates in Angiocath group received Atropine (100 vs. 76%, p = 0.002) and Fentanyl (98 vs. 36%, p < 0.001) than the MAC group.The procedural success was 91% in the Angiocath group and 89% in the MAC group (p > 0.99). Multiple attempts were needed in 24% of neonates in the Angiocath group and 37% in the MAC group (p = 0.158). More episodes of desaturations were noted in the Angiocath group (89%) than the MAC group (69%; p = 0.012). Other rates of common adverse effects were similar between the two groups. On exploratory analysis fentanyl use held significant association with less success, more desaturation, apneic episodes, and need of positive pressure ventilation /intubation.Conclusion The overall procedural success of MIST is similar in both catheter groups. The proportion of neonates requiring multiple attempts was lower with the Angiocath, though difference was not statistically significant. Desaturation episodes were seen more frequently in the Angiocath group, which was related to higher use of procedural sedation in this group.Key Points
Keywords: neonates; surfactant; minimally invasive; multiaccess catheter; angiocath